Detail specification for solder-sealed quartz crystal units for oscillator applications. AA, CX and BC/1 enclosures, 50 to 125 MHz frequency range. Fifth overtone thickness-shear mode, AT-cut, for operation over narrow temperature ranges (temperature controlled). Full assessment level. (15th June 1977) - British Standards Institution,
No abstract available